This is Africa: Whiteness and Representations of the other recent Hollywood Films - Swank, Allison (African Studies, 2014)
This mini-dissertation interrogates racial representations in two recent Hollywood films, The Last King of Scotland (2006) and Blood Diamond (2006). Drawing heavily from Richard Dyer's key theories on the white heterosexual male image in film, I look specifically at representations of whiteness in both films' male protagonists: Dr. Nicholas Garrigan (Last King) and Danny Archer (Blood Diamond). Both men use the phrase, 'This is Africa' (TIA) in conversation with white foreigners to enunciate some supposedly enduring characteristics of Africa that mark its essential difference from what exists in a normative elsewhere that is never explicitly mentioned. Using Edward Said's 'strategic location' (1978:20) as a method of discourse analysis, I examine the narrative positions of both men as they appropriate TIA discourse. In doing so, I unpack TIA discourse to reveal its reflection of colonial discourse as well as the new knowledges it produces. This work is divided into four chapters. The first chapter focuses on the knowledge regime on which TIA discourse is anchored while the second chapter sketches a history of this knowledge regime through its representation on screen. The second chapter also describes how the socio-political context of time and space largely effect race representations in Hollywood films. Chapter 3 focuses on the narrative position of the white male heterosexual protagonist, Dr. Nicholas Garrigan as he articulates and appropriates TIA discourse in The Last King of Scotland (2006). Chapter 4 focuses on the same principles of Chapter 3, except with the white male heterosexual protagonist of Blood Diamond (2006), Danny Archer. The final chapter resubmits the theories of TIA discourse I put forth and concludes my intervention. [W]hen we desire to decolonize minds and imaginations, cultural studies' focus on popular culture can be and is a powerful site for interventions, challenge, and change... only if we start with a mind-set and a progressive politics that is fundamentally anticolonialist, that negates cultural imperialism in all its manifestations" (hooks 1994:4,6).